Living Walls - Aitor Frías-Sánchez; Joaquín Perailes-Santiago; Diego Jiménez-López (Footprint)
In her acclaimed science fiction trilogy Xenogenesis, Octavia E. Butler presents a narrative of interspecies coexistence involving humans and the alien Oankali. This coexistence is facilitated by living entities known as Lo, which serve as dynamic architectures mediating positive, mutualistic interactions between the two species. These entities offer a valuable framework for analysing architectures that seek to integrate the other. In this article, we propose to extend existing debates on interspecies co-design practices and link them to the concept of xenoarchitecture. Furthermore, we propose the Interspecies Interaction Protocols (IIP) to regulate human/other-than-human interactions in built environments. To demonstrate that xenoarchitecture’s interspecies mediating vision can be applied to non-fictional real-world architecture, we project ideas from Butler’s onto three unusual examples of buildings that achieve this human/other-than-human mediation: the library at the National Palace of Mafra and Coimbra University’s Joanina Library, both located in Portugal, and the Karni Mata temple, located in Rajasthan, India. These case studies illustrate positive IIPs that facilitate mutualistic coexistence between humans and two other species, bats and rats.